Winter's tail How one little Dolphin learned to swim again - Hatkoff, Juliana; Hatkoff, Craig; Hatkoff, Isabella (New York Scholastic, 2009)
When Winter was a baby, she was rescued from a crab trap, her tail seriously damaged, and rushed to Clearwater Marine Aquarium. Winter survived, but eventually her tail fell off. Then Winter received a prosthetic tail. It was very challenging but now Winter is thriving and using her new tail with great command. Every year, thousands of visitors travel to visit Winter who has become an inspiration to adults and children alike, especially to children who are amputees themselves. And now Winter's story is soon to be a major motion picture starring Morgan Freeman, Ashley Judd, and Harry Connick Jr.!
From the #1 New York Times bestselling Authors of owen & Mzee
Science (Marine Creature)
The story that inspired the new Major Motion Picture!
Keywords: Aquatic ecology